The Comparative of Advertising Effectiveness between TV Advertising and Digital Advertising - Rahma Luthfi Wilujeng (Prosiding Industrial Research Workshop and National Seminar, 2018)
This study aims to compare the effectiveness of advertising and see if there are differences in two different media:digital media (Social media, Youtube, website, etc.) and TV. For this purpose, the AIDA model was employed as thebasis for comparison. This study uses questionnaire methodology to collect data. Total respondents who participatedwere 230 for TV responders and 171 for digital media using Purposive Sampling technique. The result of this researchthere is differences between respondent's Interest and Desire on digital and TV advertising. The average value ofattention, interest, desire and action is higher on digital media than on TV. This can be of more concern to advertisersfor the effectiveness of their advertising.